2017
DOI: 10.1371/journal.pgen.1006596
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of resistance and matching-allele interactions of a host-parasite system: The Daphnia magna-Pasteuria ramosa model

Abstract: Negative frequency-dependent selection (NFDS) is an evolutionary mechanism suggested to govern host-parasite coevolution and the maintenance of genetic diversity at host resistance loci, such as the vertebrate MHC and R-genes in plants. Matching-allele interactions of hosts and parasites that prevent the emergence of host and parasite genotypes that are universally resistant and infective are a genetic mechanism predicted to underpin NFDS. The underlying genetics of matching-allele interactions are unknown eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
152
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(171 citation statements)
references
References 35 publications
16
152
3
Order By: Relevance
“…The infection genetics in this system is therefore consistent with the matching allele (MA) model of infection (Grosberg and Hart ; Bento et al. ) and is known to exhibit FS dynamics in the long term (Decaestecker et al. ).…”
Section: Discussionsupporting
confidence: 70%
“…The infection genetics in this system is therefore consistent with the matching allele (MA) model of infection (Grosberg and Hart ; Bento et al. ) and is known to exhibit FS dynamics in the long term (Decaestecker et al. ).…”
Section: Discussionsupporting
confidence: 70%
“…Only the attachment step, however, perfectly correlated with the genotype of the host. Our results confirm previous studies that the ability of the pathogen to attach to the host oesophagus was an all‐or‐nothing affair (Bento et al, ; Duneau et al, ), with all individuals of a host recombinant line either allowing complete parasite attachment or not (Figure a). In contrast, variation in the subsequent success of the pathogen in establishing infection was more variable (Figure b), with the probability of all replicates of a susceptible host line becoming infected varying continuously between 0 and 1 (mean = 0.80; SD = 0.21).…”
Section: Resultssupporting
confidence: 92%
“…Here, we use a quantitative trait locus (QTL) approach to identify the chromosomal regions underlying the components of the defence cascade, from the initial contact between the host and pathogen, to the transmission of the pathogen at host death. Work on the highly specific step underlying host susceptibility has already revealed that this attachment step is under the control of a limited number of regions in the host genome (Bento et al, ; Luijckx, Fienberg, Duneau, & Ebert, ; Metzger, Luijckx, Bento, Mariadassou, & Ebert, ), consistent with the idea that the genetic architecture of this step is unlike other complex traits. Yet, the other components of the infection process remain uncharacterized.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations